Effect of Temperature on Metronidazole Resistance in Helicobacter pylori - Gong, Meiliang; Han, Yingjie; Wang, Xuning; Tao, Hongjin; Meng, Fansen; Hou, Baicun; Sun, Benjamin B.; Wang, Gangshi (Frontiers in Microbiology, 2021)
Efficacy of Helicobacter pylori (H. pylori) eradication therapy has declined due to rapid rises in antibiotic resistance. We investigated how increased temperature affected H. pylori (NCTC 11637) growth and its sensitivity to metronidazole in vitro. We performed transcriptomic profiling using RNA-sequencing to identify differentially expressed genes (DEGs) associated with increased temperature. Transcriptional pathways involved in temperature-driven metronidazole resistance changes were analysed through bioinformatic and literature curation approaches. We showed that H. pylori growth was inhibited at 41C and inhibition was more apparent with prolonged incubation. Resistance to metronidazole was also reduced - minimum inhibitory concentration for metronidazole decreased from > 256 µg/ml at 37C to 8 µg/ml at 41C after culturing for 3 days. RNA-sequencing results, which were highly concordant within treatment conditions, revealed more than one third of genes (583/1,552) to be differentially expressed at increased temperatures with similar proportions up and down-regulated. Quantitative real-time PCR validation for 8 out of 10 DEGs tested gave consistent direction in gene expression changes. We found enrichment for redox and oxygen radical pathways, highlighting a mechanistic pathway driving temperature-related metronidazole resistance. Independent literature review of published genes associated with metronidazole resistance revealed 46 gene candidates, 21 of which showed differential expression and 7 out of 9 DEGs associated with “redox” resistance pathways. Sanger sequencing did not detect any changes in genetic sequences for known resistance genes rdxA, frxA nor fdxB. Our findings suggest that temperature increase can inhibit the growth and reduce H. pylori resistance to metronidazole. Redox pathways are possible potential drivers in metronidazole resistance change induced by temperature. Our study provides insight into potential novel approaches in treating antibiotic resistant H. pylori.